Synthesis of magnetic nanoparticles and microRNA sensing application - Koh, Yan Min (2014)
The morphology and size of MNPs (Magnetic Nanoparticles) are largely determined by the synthesis method and route. Rice spindle magnetite can be synthesized via co-precipitation in the absence of oxygen. Similarly, magnetite of different shapes and sizes can be oxidized to form γ-Fe2O3 (magnetic). Nanospheres MNPs have also shown promise in potential biosensors when used in conjunction with PS-PIAT (Polystyrene-b-polyisocyanoalanine (2-thiophene-3-yl-ethyl) amide) polymersomes. Successfully synthesized nanospheres and nanorice MNPs are evaluated for their size, shapes and magnetic properties using TEM (Transmission Electron Microscopy) and magnets. In addition, nanospheres MNPs are incorporated with PS-PIAT polymersomes which are encapsulated with HRP (horseradish peroxidase) for colorimetric detection of cancer biomarker microRNA. Based on the color changes upon the addition of substrates, one is able to distinguish the presence of microRNA. Viability of the biosensor is optimized using different substrates such as ABTS (2,2’- azino – bis (3 – ethylbenzthiazoline - 6 - sulfonic acid)) and Ampliflu Red indicators via absorbance and/ or fluorescence tests. The MNPs provides a possibility to capture and purify the analytes from complex matrix such as blood and urine samples. Furthermore, the polymersomes are able to maintain the activity of enzyme inside of the nano-chamber and allow small molecules such hydrogen peroxide diffusing in/out of the polymersomes. This method paves a way for the colorimetric detection of microRNA in real samples.